2011
DOI: 10.1021/jp207528p
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Dynamics of Coumarin-153 and 4-Aminophthalimide in 1-Ethyl-3-methylimidazolium Alkylsulfate Ionic Liquids: Effect of Alkyl Chain Length on the Rotational Dynamics

Abstract: Rotational dynamics of two neutral organic solutes, coumarin-153 (C-153) and 4-aminophthalimide (AP), with only the latter having hydrogen-bond-donating ability, has been investigated in a series of 1-ethyl-3-methylimidazolium alkyl sulfate ionic liquids as a function of temperature. The ionic liquids differ only in the length of the linear alkyl side chain (alkyl = ethyl, butyl, hexyl, and octyl) on the anionic moiety. The present study has been undertaken to examine the role of alkyl side chains on the rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(122 citation statements)
references
References 58 publications
8
114
0
Order By: Relevance
“…[73] When the rotatings olute molecule is larger in size than the solvent molecule, C is unity (stick boundary condition).Inthe case of asolute molecule that is of asize comparable to or smaller than the solventm olecule, C is less than unity.T he shapes of the solute molecules are usually considered to be symmetrical or asymmetricale llipsoids in this theory. [32] The slip and stick boundary limits that were assigned with the help of SED hydrodynamic theory are shown in Figure 7w ith the experimentally measuredr eorientation times of C153 in the presentI Ls. For the calculation of the slip boundaryc ondition C slip , C153 is considered to be an asymmetricale llipsoid in determining the theoretical rotational time, and we took the probe properties that are already available in the literature.…”
Section: Time-resolveds Tudiesmentioning
confidence: 71%
See 3 more Smart Citations
“…[73] When the rotatings olute molecule is larger in size than the solvent molecule, C is unity (stick boundary condition).Inthe case of asolute molecule that is of asize comparable to or smaller than the solventm olecule, C is less than unity.T he shapes of the solute molecules are usually considered to be symmetrical or asymmetricale llipsoids in this theory. [32] The slip and stick boundary limits that were assigned with the help of SED hydrodynamic theory are shown in Figure 7w ith the experimentally measuredr eorientation times of C153 in the presentI Ls. For the calculation of the slip boundaryc ondition C slip , C153 is considered to be an asymmetricale llipsoid in determining the theoretical rotational time, and we took the probe properties that are already available in the literature.…”
Section: Time-resolveds Tudiesmentioning
confidence: 71%
“…The two extreme marginal conditions are stick and slip according to this hydrodynamic theory. [32] The van der Waals volume, shape factor,a nd calculated slip boundary condition parameter for C153 are 243 3 ,1 .5, and 0.18 respectively. For nonspherical molecules, f is generally greater than unity and the extento fd eviation from unity in the value of f describes the degree of nonspherical nature of the rotating species.…”
Section: Time-resolveds Tudiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Nevertheless, viscosities of the ionic liquids have also been altered by increasing the length of the alkyl chain on one of the ions in quite a few studies. [17][18][19][20][21][22][23][24][25]39 In a majority of instances, it has been observed that the experimentally measured reorientation times did not comply with the trends predicted by the Stokes− Einstein−Debye (SED) hydrodynamic theory. 43,44 In other words, τ r versus η/T plots displayed a significant degree of nonlinearity, and also τ r values at a given η/T, especially for nonpolar and dipolar solutes, are found to be lower in ionic liquids with longer alkyl chains.…”
Section: Introductionmentioning
confidence: 99%